Investigation of the Criminal Suspects in Local Population Through Forensic Indicators, A Cross-Sectional Study - Muhammad Bilal Khan, Aliya Abrar, Ishtiaque Ali Langah, Abdul Samad, Ijaz Aziz, Faqir Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
The aims and objectives of current study were to identify the real criminal persons from suspects through modern scientific forensic technology. Methodology: A wooden stick, assaulted person’s cloth with blood strains, blood strains on the ground and some hairs from the hand of victim were collected at crime scene. And samples of accused ones were also collected. Dry blood sample was collected from the crime scene by Bloodstain Pattern Analysis while 3ml blood sample of 100 office employees were taken in the tube and was centrifuged at x10000 rpm for analysis and DNA profiling. Fingerprints were analyzed from the wooden stick by Latent printing and were compared to suspects. DNA sample also collect from hair follicle for analysis. Results: DNA profiling of Aggravated Assault on different biological aspects were analyzed, the analysis were showed that blood strains on assaulted person’s cloth has cross matching regression stranded mean deviation (1.0± 0.01) with office employees and blood strains collected from ground also have cross matched correlation with (3.0± 0.03) suspects respectively. The mitochondrial DNA of hair follicles which was in hands of Aggravated Assault at the time of crime scene has a significant (P<0.05) cross match with suspects (2.10± 0.02) DNA. Conclusion: The findings of this study through biological and non-biological aspects were significant (P<0.05). Total five persons were marked as criminal from all selected suspects by considering their DNA profile cross matching and finger prints cross match correlations with Aggravated Assault.